O-Glucoside of natural cleomiscosin-A: An attenuator of pro-inflammatory cytokine production. (August 2018) - Begum, Ahil Sajeli; Kumar, S. Santhosh; Gottapu, Suryanarayana; Hira, Kirti
Graphical abstract: Highlights: O-glucoside of cleomiscosin-A (CAG) was synthesised from natural cleomiscosin-A (CA). Inhibition effect of CAG and CA were tested against TNF-α, IL-6 and IL-1β using ELISA. CAG significantly inhibited IL-6 and IL-1β (IC50 −7.94 and 45.76 μM, respectively). Under mouse endotoxemia model CAG showed 5-fold rise in TNF-α inhibition than CA. Abstract: The study was aimed to improve the hydrophilic property and pro-inflammatory cytokine inhibitory effect of cleomiscosin-A (CA), a naturally occurring coumarinolignan in plants. In view of this, O-, N- and S-glucosides of cleomiscosin-A was designed and docking studies were performed for TNF-α protein. All derivatives showed considerable docking scores in the range of −8.433 to −9.401 kcal/mol compared to a standard TNF-α inhibitor. The O-glucoside of cleomiscosin-A (CAG) was synthesized by reacting natural cleomiscosin-A (CA) with acetobromo-α-d -glucose and pyridine. The formed product was confirmed through APCI-MS and proton NMR analysis. Inhibition effect of CA and CAG against TNF-α, IL-6 and IL-1β secretions was determined on lipopolysaccharide-induced RAW 264.7 cells using ELISA kits. CAG was potentially inhibitory against IL-6 and IL-1β secretions exhibiting IC50 values of 7.94 and 45.76 μM, respectively. Also, in-vivo (mouse endotoxemia model) performance of CAG (oral administration) in inhibiting TNF-α expression was significant (52.03% and 29.23% at 50 and 25 mg/kg body weight, respectively), demonstrating five-fold increase in activity compared to CA. In addition, CAG reduced LPS-induced NO levels and was found to be weakly cytotoxic (IC50  > 150 μM). This is the first report of semi-synthesis and pro-inflammatory cytokine inhibition effect of a coumarinolignan glucoside.